Factors Affecting the Work Engagement of Healthcare Workers during the COVID-19 Pandemic - Erlian Indah Mustikawati; Ernawaty Ernawaty (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
The COVID-19 Pandemic is a challenge for the world and, foremost, the healthcare system. The high intensity of work, the high risk of exposure, and the mental burden due to COVID-19 can affect the work engagement of healthcare workers. Healthcare worker engagement tends to be low. This research aimed to identify the factors that affect the work engagement of healthcare workers during the COVID-19 Pandemic. This research was a scoping review study conducted in December 2022. The keywords used were